Evaluation of pediatric patients with palpitations via cardiac event recorder, Holter monitoring and transesophageal electrophysiologic study in detecting arrhythmia - Ekşi, Neslihan; Ertuğrul, İlker; Akın, Alper; Aykan, Hayrettin Hakan; Yıldırım Baştuhan, Işıl; Karagöz, Tevfik; Çeliker, Alpay; Özkutlu, Süheyla; Alehan, Dursun; Aypar, Ebru; Özer, Sema (Acta Medica, 2024)
Objective: Palpitations are a common reason for referral to pediatric cardiologists, the diagnostic workup involves ambulatory, non-invasive recording devices and invasive procedures. We aimed to evaluate arrhythmic symptoms of pediatric patients with a cardiac event recorder, Holter monitoring and transesophageal electrophysiologic study (TEEPS) results. Materials and Methods: Retrospective evaluation of pediatric patients who fitted an event recorder at tertiary University Hospital between January 2002 and August 2012. The data obtained from the same patients’ as cardiac event recorder, Holter monitoring and TEEPS results were studied for comparison. Results: During the study period, 40 patients who had all data of cardiac event recorder, Holter monitoring and TEEPS were included. The median age of the patients included in the study was 12 [interquartile range, 7-15] years. Using the Holter monitoring, supraventricular extrasystoles (SVEs) were detected in six (15%) patients and ventricular extrasystoles (VESs) in three (7.5%). According to the event recorder data of the 40 patients, there was sinus tachycardia in 20 (50%), supraventricular tachycardia (SVT) in three (7.5%), and SVEs in two (5%) patients. The event recorder data of the remaining 15 patients were assessed as normal. The analysis of the TEEPS results revealed atrioventricular nodal reentrant tachycardia in four (10%), atrioventricular reentry tachycardia in three (7.5%), and normal results in the remaining 33 (82.5%) patients. Conclusions: This study demonstrated that a cardiac event recorder may also be considered as an important diagnostic tool in the diagnosis and ruling out of SVT in pediatric patients for whom the cause of arrhythmia cannot be identified with the Holter monitor, in patients who do not accept the use of TEEPS method following the use of Holter monitor, and in patients in whom SVT cannot be stimulated by TEEPS yet complaints persist.